Speech therapy intervention in patients with attention deficit hyperactivity disorder (ADHD): literature review (Research, Society and Development, 2021)
The present study deals with a literature review on Speech Therapy Intervention in patients with attention deficit and hyperactivity disorder (ADHD), aims to identify speech therapy interventions in patients with Attention Deficit / Hyperactivity Disorder (ADHD). a developmental psychiatric disorder more common in childhood, feeling a neurobiological condition that affects 3% to 7% of the population.The study sought to characterize the Attention Deficit and Hyperactivity Disorder, describing the Speech-Language Pathology alterations found in the ADHD Speech-Language Pathology in patients with ADHD, in addition to aspects related to the characteristics, diagnoses and treatment of the disorder.The speech therapy intervention aims to reduce the various compromises, positively helping these people to overcome their difficulties.The SCIELO, LILACS and MEDLINE databases were used in the years of 2010 to 2020 for data analysis. greater time frame considered that the articles found recently did not correspond to the research objective. Given the above, it is concluded that a wide spectrum of methodologies in the investigated programs, such as the use of computerized activities, training for parents and teachers, psychosocial interventions and challenging tasks within the classroom. However, there is a need for current research, considering the theme presented.